Analysis of the Influence of Mobile Banking and Financial Inclusion on the Financial Performance of Sharia Banks in Indonesia for the Period 2014-2019 - Dahayu Bethari Widyandri; Nisful Laila (Universitas Airlangga, 2022)
ABSTRAK Digitalisasi perbankan dilakukan demi pemanfaatan teknologi sehingga melahirkan mobile banking yang dapat memperluas jangkauan layanan keuangan dan Inklusi keuangan menjadi penting untuk menunjukan seberapa besar jasa layanan keuangan yang telah dipakai dan digunakan oleh masyarakat. Penelitian ini bertujuan untuk menguji dan menganalisis pengaruh mobile banking dan keuangan inklusif terhadap kinerja keuangan bank Syariah di Indonesia. Penelitian ini memakai 11 sampel Bank Umum Syariah dan diuji menggunakan Regresi Data Panel dengan variable independent keuangan inklusi yang diukur dengan ROA, ROE, dan BOPO. Hasilnya didapatkan bahwa mobile banking berpengaruh terhadap kinerja keuangan bank Syariah dan keuangan inklusi berpengaruh terhadap kinerja keuangan yang di proksikan dengan Dana Pihak ketiga dan Jaringan kantor namun Pembiayaan tidak berpengaruh terhadap kinerja keuangan. Bagi Regulator, agar menedukasi atau memberikan penyuluhan tentang literasi dan inklusi keuangan untuk masyarakat Indonesia agar masyarakat merasakan manfaat dari layanan keuangan perbankan. Bagi bank umum Syariah, agar memperluas jaringan mobile banking secara maksimal sehingga dapat meningkatkan kinerja keuangan bank Syariah di Indonesia dan menjadi pertimbangan bagi para manajemen untuk melakukan investasi di mobile banking untuk meningkatkan profitabilitas bank Syariah secara jangka Panjang. Kata Kunci: Mobile Banking, Keuangan Inklusi, Kinerja Keuangan. ABSTRACT Digitalization of banking is done for the use of technology so as to give birth to mobile banking that can expand the reach of financial services and financial inclusion becomes important to show how much financial services have been used and used by the public. This study aims to test and analyze the influence of mobile banking and inclusive finance on the financial performance of Sharia banks in Indonesia. This study used 11 samples of Sharia Commercial Banks and tested using Regression Data Panel with independent financial inclusion variables as measured by ROA, ROE, and BOPO. The result was obtained that mobile banking affects the financial performance of Sharia banks and financial inclusion affects the financial performance proxies with third party funds and office networks but financing has no effect on financial performance. For regulators, in order to educate or provide counseling on financial literacy and inclusion for the people of Indonesia so that the public can feel the benefits of banking financial services. For Sharia commercial banks, in order to expand the mobile banking network to the maximum so as to improve the financial performance of Sharia banks in Indonesia and be a consideration for management to invest in mobile banking to improve the profitability of Sharia banks in the long term. Keywords: Mobile Banking, Financial Inclusion, Bank Performance. DAFTAR PUSTAKA Agustiningsih, F. (2017). Analisis perbandingan dana pihak ketiga, biaya operasional terhadap pendapatan operasional, profitabilitas, likuiditas sebelum dan sesudah penerapan laku pandai (Branchless banking) pada bank BUMN periode 2013-2017. Prosiding Manajemen, 5(2), 1239-1344. http://dx.doi.org/10.29313/.v0i0.18546 Ahamed, M. M., & Mallick, S. K. (2019). Is financial inclusion good for bank stability? International evidence. Journal of Economic Behavior and Organization, 157, 403–427. https://doi.org/10.1016/j.jebo.2017.07.027 Ahyar, M. K. (2019). Analisis pengaruh inklusi perbankan syariah terhadap pembiayaan UMKM sektor halal di Indonesia. Al-Tijary, 5(1), 19–36. https://doi.org/10.21093/at.v5i1.1716 Ali, H., Abdullah, R., & Zaki Zaini, M. (2019). Fintech and its potential impact on Islamic banking and finance industry: A case study of Brunei Darussalam and Malaysia. International Journal of Islamic Economics and Finance (IJIEF), 2(1), 73–108. https://doi.org/10.18196/ijief.2116 Ali, M. M., Devi, A., Furqani, H., & Hamzah, H. (2020). Islamic financial inclusion determinants in Indonesia: an ANP approach. International Journal of Islamic and Middle Eastern Finance and Management, 13(4), 727–747. https://doi.org/10.1108/IMEFM-01-2019-0007 Azwar, A. A. (2017). Analisis empiris inklusifitas keuangan syariah di Indonesia. Jurnal BPPK: Badan Pendidikan Dan Pelatihan Keuangan, 10(1), 1–21. https://doi.org/10.48108/jurnalbppk.v10i1.21 Brigham, E. F. dan J. F. H. (2001). Manajemen keuangan. Jakarta: Erlangga. Buse, S., & Buse, S. (2007). Mobile Services in Banking Sector: The Role of Innovative Business Solutions in Generating Competitive Advantage. Proceedings of the International Research Conference on Quality, Innovation and Knowledge Management, 886-894. Chatterjee, A. (2020). Financial inclusion, information and communication technology diffusion, and economic growth: a panel data analysis. Information Technology for Development, 26(3), 607–635. https://doi.org/10.1080/02681102.2020.1734770 Del Gaudio, B. L., Porzio, C., Sampagnaro, G., & Verdoliva, V. (2020). How do mobile, internet and ICT diffusion affect the banking industry? An empirical analysis. European Management Journal, 39(3), 327-332. https://doi.org/10.1016/j.emj.2020.07.003 Deyoung, R., Lang, W. W., & Nolle, D. L. (2007). How the Internet affects output and performance at community banks. Journal of Banking & Finance, 31(4), 1033–1060. https://doi.org/10.1016/j.jbankfin.2006.10.003 Mastuti, D. F. A., & Indriyani, F. (2021). Peran mobile banking dan keuangan inklusi terhadap peningkatan profitabilitas perbankan syariah di indonesia. Bulletin of Management & Business, 2(1), 25–37. Global Findex. (2018). The little data book on financial inclusion 2018. Washington DC: Worldbank. Hajhashem, M., & Khorasani, A. (2015). Demystifying the dynamic of disruptive innovations in markets with complex adoption networks: From encroachment to disruption. International Journal of Innovation and Technology Management, 12(5), 1–22. https://doi.org/10.1142/S0219877015500224 Hanivan, H., & Nasrudin, N. (2019). A financial inclusion index for Indonesia. Buletin Ekonomi Moneter Dan Perbankan, 22(3), 351–366. https://doi.org/10.21098/bemp.v22i3.1056 Harelimana, J. B. (2018). Impact of mobile banking on financial performance of Unguka microfinance bank Ltd, Rwanda. Journal of Harmonized Research in Management, 4(1), 26. https://doi.org/10.30876/johr.4.1.2018.26-40 Hernando, I., & Nieto, M. J. (2006). Is the Internet delivery channel changing banks’ performance ? The case of Spanish banks. Journal of Banking & Finance, 31(4), 1083-1099. https://doi.org/10.1016/j.jbankfin.2006.10.011 Hidayati, A. N. (2016). Pengaruh inflasi, bi rate dan kurs terhadap profitabilitas bank syariah di Indonesia. An-Nisbah: Jurnal Ekonomi Syariah, 1(1), 72-97. https://doi.org/10.21274/an.2014.1.1.72-9746. Kara, M. (2008). Konstribusi pembiayaan perbankan syariah terhadap pengembangan usaha mikro, kecil, dan menengah. Ahkam: Jurnal Ilmu Syariah, 13(2), 315–322. Karjaluoto, H., Hepola, J., & Lepp, M. (2020). Is it all about consumer engagement ? Explaining continuance intention for utilitarian and hedonic service consumption. Journal of Retailing and Consumer Services, 57(April). https://doi.org/10.1016/j.jretconser.2020.102232 Lashitew, A. A., van Tulder, R., & Liasse, Y. (2019). Mobile phones for financial inclusion: What explains the diffusion of mobile money innovations? Research Policy, 48(5), 1201–1215. https://doi.org/10.1016/j.respol.2018.12.010 Laukkanen, T., Sinkkonen, S., Kivijärvi, M., & Laukkanen, P. (2007). Innovation resistance among mature consumers. Journal of Consumer Marketing, 24(7), 419–427. https://doi.org/10.1108/07363760710834834 Margaretha, F. (2015). Dampak electronic banking. Jurnal Keuangan Dan Perbankan, 19(3), 514–524. Nila, J., & Mustika, Noor Mifrahi Achmad, T. (2017). Faktor-faktor yang mempengaruhi deposito mudharabah pada bank syariah di Indonesia. Jurnal Ekonomi dan Keuangan Islam, 3(1). https://doi.org/10.20885/jeki.vol3.iss1/art5 Ouma, S. A., Odongo, T. M., & Were, M. (2017). Mobile financial services and financial inclusion: Is it a boon for savings mobilization? Review of Development Finance, 7(1), 29–35. https://doi.org/10.1016/j.rdf.2017.01.001 Reuters, T. and D. (2018). Your gateway into the Islamic economy. An Inclusive, Ethica, Economy,Global Islamic Economy Report 2018/19. http://www.gifr.net/gifr2013/ch_13.PDF Sarah, H. (2013). Dampak branchless banking terhadap kinerja keuangan PT Bank Muamalat Indonesia. Al-Muzara'ah, 3(2), 136-157. https://doi.org/10.29244/jam.3.2.136-157 Sarma, M. (2015). Measuring financial inclusion. Economics Bulletin, 35(1), 604–611. Shaikh, I. M., Qureshi, M. A., Noordin, K., Shaikh, J. M., Khan, A., & Shahbaz, M. S. (2020). Acceptance of Islamic financial technology (FinTech) banking services by Malaysian users: an extension of technology acceptance model. Foresight, 22(3), 367–383. https://doi.org/10.1108/FS-12-2019-0105 Siddik, N. A., Sun, G., Kabiraj, S., Shanmugan, J., & Yanjuan, C. (2016). Impacts of e-banking on performance of banks in a developing economy: Empirical evidence from Bangladesh. 17(6), 1066–1080. https://doi.org/10.3846/16111699.2015.1068219 Sinambela, E., & Rohani. (2017). Pengaruh penyediaan layanan internet banking terhadap kinerja keuangan perbankan di Bursa Efek Indonesia. Forum Keuangan Dan Bisnis Indonesia (FKBI), 6, 87–94. http://fkbi.akuntansi.upi.edu/ Umar, A. I. (2017). Index of Syariah Financial Inclusion in Indonesia. Buletin Ekonomi Moneter Dan Perbankan, 20(1), 99–126. https://doi.org/10.21098/bemp.v20i1.726 Vo, D. H., Nguyen, N. T., & Thi-Hong Van, L. (2020). Financial inclusion and stability in the Asian region using bank-level data. Borsa Istanbul Review. https://doi.org/10.1016/j.bir.2020.06.003 World Bank. (2018). World bank report 2018. Washington DC: World Bank.